Cotidiano e cultura: a dinâmica da organização social na Vila de Paricatuba no Amazonas - Silva, Elane Cristina Lima da (2018)
This thesis aims to analyze the community relations occured in daily lives of rural social groups from Paricatuba village, located in the Amazon. It was analyzed its social organization in order to access social services. For this purpose, a survey was conducted in order to map the social assets and services existing in the village. It was identified the key strategies on social organization to reach health and education services, with focus on the daily lives of rural social groups. It was studied the socio-cultural aspects that resist and compose the local resident´s social organization. Thinking on the greatness of Brazilian Amazon, specifically the state of Amazon in the north of the country, requires considering rural population that live along the bank of rivers and their tributaries, people who suffer of impoverishment, denial of rights and reliance on the government's handouts. Despite this, such people live in a social organization that allow their social production which is combined with nature and cultural codes generators that permeate their way of life. Thus, in order to develop such research in the city of Iranduba, more precisely at Paricatuba village, included analysing a natural and singular community dynamics, which stands out for socio-cultural practices that give them and ordering along their everyday life and the existing goods and social services on site. We have found out that the population face hostile and adverse economic and political context, especially in regard to difficult access to social policies, and poor transfer of public funds allocated for essential services of the village. Moreover due to the advancement of the consumer society which has materialized especially with construction of the bridge journalist Phelippe Daou. According to the methodological perspective, the study has critical-analytical character and qualitative approach. We made bibliographic and documentary research to base the theoretical framework, and used a set of techniques and instruments in the field of study, such as: obtaining narrative testimonials, observation of participants, use of photographic records and notes on the field. It has been discovered a micro Amazon world in changing process, which is linked through a singular social organization, expressed in an everyday life permeated by culture that reflects the strength and preservation of its way of life. Despite this, it has inevitably absorbed the references originated from the economic system in force